ГАРМОНІЗАЦІЯ ЄВРОПЕЙСЬКОГО КОЛІЗІЙНОГО ТА МАТЕРІАЛЬНОГО ПРАВА У СФЕРІ ЗАХИСТУ ПРАВ СПОЖИВАЧІВ - Саванець, Людмила (Актуальні проблеми правознавства, 2017)
Саванець Л. Гармонізація європейського колізійного та матеріального права у сфері захисту прав споживачів. Досліджено питання гармонізації європейського колізійного та матеріального права в сфері захисту прав споживачів. Акцентовано увагу на сучасному acquis communautaire з європейського споживчого права. Проаналізовано окремі аспекти колізійного права Європейського Союзу щодо захисту прав споживачів. З’ясовано сучасні тенденції Європейського Союзу до зміни типу мінімальної гармонізації європейського законодавства у сфері захисту прав споживачів на повну гармонізацію. Саванец Л. Гармонизация европейского коллизионного и материального права в сфере защиты прав потребителей. Исследовано вопрос гармонизации европейского коллизионного и материального права в сфере защиты прав потребителей. Акцентируется внимание на современном acquis communautaire с европейского потребительского права. Проанализированы отдельные аспекты коллизионного права Европейского Союза по защите прав потребителей. Выяснено современные тенденции Европейского Союза к изменению типа минимальной гармонизации европейского законодательства в сфере защиты прав потребителей на полную гармонизацию. Savanets L. Harmonisation of European confict law and substantive law in the feld of consumer protection. The article investigates the issue of harmonization of European conflict law and substantive law in the field of consumer protection. The author focuses on the present acquis communautaire of European consumer law. Some aspects of EU conflict law on consumer protection are analyzed. Current trends of the EU to change the type of minimum harmonization of European legislation on consumer protection on full harmonization are founded. Legal analysis which was conducted, leads to the conclusion that presently, the basis for harmonization of European conflict law and substantive law in the area of consumer protection is the Rome I Regulation and the Brussels I Regulation, Directive 2011/83/EC on consumer rights and a Proposal for a Regulation on Common European Sales Law. European legislator for consumers’ protection preferred type of minimum harmonization. National legal system had freedom to provide higher level of consumers’ protection. However, in recent years the type of consumers’ law harmonization changed with the minimum to full. This provides the same level of consumers’ protection in all EU Member States. The fundamental principle of the Rome I Regulation is freedom of the parties in choice of law that will regulate the contractual relationship. This principle may be limited in relation to consumer contracts in order to ensure a higher level of consumers’ protection with ordinary and preferred mandatory provisions. Directive 2011/83/EU on consumer rights, like all laws passed in the EU member states for the purpose of the implementation of its provisions, is an important step towards the harmonization of consumer law in Europe. Adoption the Directive 2011/83/EU on consumer rights was the basis for the introduction of a common and uniform legal regulation in the sphere of consumer law, increased consumer protection in the EU. However, the questions of the scope of Directive 2011/83 / EU on consumer rights are insufficiently understood. Regarding contracts traditionally are not considered as sales contracts in the Member States law. The next problem is the possibility of using consumers’ ways to protect the rights and interests laid down in the general provisions of contract law EU member states, along with those defined in the Directive. Construction of Directive 2011/83 / EC on consumer rights on the type of full harmonization determines the problem of uncertainty in the law. Indeed, there was a full harmonization of consumer law without similar harmonization of general contract law rules.